Strengthening Language and Literature Competencies of High School Student - Esti Ismawati; Joko Sungkono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The scientific approach and contextual teaching which is widely used in science learning has not been widely used in language learning, especially in the 2016 Indonesian Language and Literature Curriculum. This study aims to analyze the relationship between the application of a scientific approach and contextual teaching in the application of the 2016 Indonesian language and literature curriculum with the achievement of learning Indonesian language and literature for class X SMA students. This study uses a type and quantitative research approach with surveys with correlational techniques. The research subjects were students of senior high school. Samples were taken randomly in class X. Data collection method uses in this study are observation, documentation, and interview. The research instruments were interviews and objective tests and essays which had been tried out before being used. Data analysis techniques used are product moment correlation, partial correlation, and double regression. From the results of the analysis, it can be concluded that there is a significant relationship between the use of SA and CTL together with achievement in learning Indonesian Language and Literature (score above 78). The implication of this research is the importance of using SA and CTL in private schools that have not used these two approaches in learning.